Digital Transformation Success in the UAE: The Impact of Leadership, Organizational Flexibility, and Strategic Planning Based on Structural Equation Modeling - Sakka, Fadi (Comparative Economic Research. Central and Eastern Europe, 2026)
This study explores the relationship between leadership, organizational flexibility, and strategic planning, and the power of these elements to promote successful digital transformation in the context of the United Arab Emirates. This quantitative study involves the use of surveys and questionnaires that were distributed to 1000 mid-to-senior-level managers. Data on 600 valid answers (representing a response rate of 60%) were analyzed with Structural Equation Modelling (SEM) using AMOS software. The research examines three primary concepts: Leadership, Organizational Flexibility, and Strategic Planning, and how they influence the achievement of Successful Digital Transformation. The findings reveal that 82% of participants said that visionary leadership is essential for digital transformation, 78% stressed the need to effectively communicate goals, and 81% emphasized motivating employees. Furthermore, 75% of the participants said that their businesses had the capacity to adjust to changes, while 73% acknowledged the presence of flexible work practices, and 80% emphasized the need for cross-functional cooperation. Of the 77% of respondents who stated that their firms have a clearly defined digital strategy, 79% had aligned their digital strategy with their company goals, and 74% had included quantifiable targets and key performance indicators (KPIs). These results emphasize the significance of integrating artificial intelligence and data analytics with effective human leadership and strategic planning. It is suggested that organizations enhance their leadership capabilities, foster a flexible culture, and develop comprehensive digital strategies to reap the benefits of digital transformation to the maximum.